2007
DOI: 10.1002/jmv.21029
|View full text |Cite
|
Sign up to set email alerts
|

Poly(γ‐glutamic acid) nanoparticles as an efficient antigen delivery and adjuvant system: Potential for an AIDS vaccine

Abstract: Antigen delivery systems using polymeric nanoparticles are of special interest as stable protein‐based antigen carriers. In the present study, novel biodegradable poly(γ‐glutamic acid) (γ‐PGA) nanoparticles were examined for their antigen delivery and immunostimulatory activities in vitro and in vivo. The uptake of ovalbumin by dendritic cells was markedly enhanced by γ‐PGA nanoparticles, and the ovalbumin was gradually released from γ‐PGA nanoparticles into the cells. In addition, γ‐PGA nanoparticles appeared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(41 citation statements)
references
References 32 publications
(36 reference statements)
1
40
0
Order By: Relevance
“…Various polymers have been demonstrated to have such properties, such as polylactic acid (PLA), poly (lactide-co-glycolide) acid (PLGA) [206,207], chitosan [208][209][210][211] or modified chitosan [207], poly(-glutamic acid) (-PGA) [212,213], polypeptides [204], starch [214,215], polystyrene [35,205], polyphosphazene [216], poly (prolylene sulfide) [217], polyethylene glycol [218], alginate [219], and their copolymers [220,221]. They enhance immunogenicity through several mechanisms, including enhancement of antigen uptake by dendritic cells (in vitro) [212], maturation of dendritic cells [212], promotion of proliferation of antigen-specific T cells [212], stimulation of both B and T lymphocytes [208], facilitation of activation of dendritic cells [222], viscosity-induced retention of antigens in the vaccination site [210] and controlled release of antigen by particles [223,224]. Uptake of such nanoparticulates could take place by DCs through both clathrin and pinocytic pathwasys [217].…”
Section: Polymeric Solutions or Particulatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Various polymers have been demonstrated to have such properties, such as polylactic acid (PLA), poly (lactide-co-glycolide) acid (PLGA) [206,207], chitosan [208][209][210][211] or modified chitosan [207], poly(-glutamic acid) (-PGA) [212,213], polypeptides [204], starch [214,215], polystyrene [35,205], polyphosphazene [216], poly (prolylene sulfide) [217], polyethylene glycol [218], alginate [219], and their copolymers [220,221]. They enhance immunogenicity through several mechanisms, including enhancement of antigen uptake by dendritic cells (in vitro) [212], maturation of dendritic cells [212], promotion of proliferation of antigen-specific T cells [212], stimulation of both B and T lymphocytes [208], facilitation of activation of dendritic cells [222], viscosity-induced retention of antigens in the vaccination site [210] and controlled release of antigen by particles [223,224]. Uptake of such nanoparticulates could take place by DCs through both clathrin and pinocytic pathwasys [217].…”
Section: Polymeric Solutions or Particulatesmentioning
confidence: 99%
“…The event leads to activation of the NALP3 inflammasome, promoting innate and antigen-specific cellular immunity [77]. Such particulate adjuvants could be as effective as aluminum hydroxide [221] or even the potent complete Freund's adjuvant (CFA) [212].…”
Section: Polymeric Solutions or Particulatesmentioning
confidence: 99%
“…77,78 Delivery is a key determinant as to whether or not RNA interferencebased therapeutics will have clinical relevance and delivery encompasses extracellular transport of the nanoplex to target cells, its intracellular RNA trafficking, and processing. [79][80][81][82][83][84][85][86][87][88][89] Gold nanoparticles are particularly attractive for therapeutic applications due to their biocompatibility and ease of complex formation with biomolecules. Gold nanorods (GNR) have far-reaching potential for the study of intracellular processes at the single-molecule level, using high-resolution cellular imaging, long-term observation of cell trafficking in vivo, and gene silencing.…”
Section: 7576mentioning
confidence: 99%
“…Wang et al 79 have shown that γ-polyglycolides (γ-PGA) nanoparticles have a capacity comparable to that of complete Freund's adjuvant (CFA) in inducing p24-specific serum antibody by predominantly activating p24-specific interferon-γ-producing T cells. Thus, γ-PGA nanoparticles encapsulating various antigens may have great potential as novel and efficient protein-based vaccines against HIV-1 infection.…”
Section: Nanoparticles As Adjuvants In Hiv Vaccinementioning
confidence: 99%
“…[9][10][11][12][13] Recent studies have proposed medical applications for PGA. [14][15][16][17][18][19] The pgsBCAywtC operon of B. subtilis (natto) directs PGA synthesis, 1,20,21) and the gene products PgsB, C, A, and YwtC are thought to form a PGA synthetase complex in the cytoplasmic membrane. 1,3) PgsB is an ADP-forming ATPase belonging to the MruD family, and is considered to have a catalytic center for polymerization.…”
Section: -3)mentioning
confidence: 99%